I Greet You a Thousand Times: A Concert for Live Orchestra with Video Projection and Audio Playback - Hodkinson, Juliana; Koester, Joachim (Berlin Hansen, 2005)
I greet you a thousand times may also be performed without video. A solo electronic version with visuals is being devised, with the composer performing a live remix together with the video by Joachim Koester.I greet you a thousand times was first performed by Odense Symphony Orchestra in Carl Nielsen Hall, Odense, Denmark, conducted by Thomas Søndergaard. The work is the result of my season as composer-in-residence with the orchestra, a residency funded by the Danish Arts Foundation. The musical score was awarded a special prize by the Danish Arts Foundation, and the full version opened the Nordic Music Days with Norrköping Symphony Orchestra in 2007, conducted by Thomas Søndergaard. In 2010, I greet you a thousand times was presented in a Hörkino version at TU Studio, Berlin.One late summer day in1868, on a walk in the Alps, Brahms found at last the theme which would later become the horn melody in his first symphony. It was to take another 8 years before he was able to complete the symphony which caused him such difficulties right from his first attempts in 1854. Still, on 12th september 1868, Brahms sent a postcard with the alphorn melody to Clara Schumann, writing under the notes: Hoch auf'm Berg, tief im Thal, grusse ich dich viel tausendmal. Brahms first symphony has since become one of the iconic representations of absolute concert music, with its striving for instrumental autonomy, separated from wordly references. The anecdotes surrounding the symphony nevertheless reveal a link to a romanticism of nature that transfers the composers world of fantasy to a sublime landscape that was beyond everyday surroundings and also far from the bourgeois concert-hall.I greet you a thousand times arose in close dialogue with Odense Symphony Orchestra. I chose to develop the work in collaboration with visual artist Joachim Koester. Our collaboration thematises and challenges the inherited concert format through exploring a number of fields of tension. Live performance is presented against the industry of recorded music. The autonomy of symphonic music is held up against the anecdotal culture surrounding Brahms First Symphony his walk in the Alps, his postcard to Clara Schumann, his Beethoven complex. The supposed neutrality of instrumental concerts is held up against the stark visual impression of its dress code and architectures. The amplified live orchestra, playing against processed audio and video recordings, is brought into a field of tension between reproduction and development. We talked about how to explore the maxim of iconic symphonic works as being timeless, and chose, by turns, to compress and stretch the audio and video recordings. The irrevocability of live concert is held up against digital medias reversibility. Music and video unfold in a study on cross-sections between the contemporary and the mediatized, between direct actions and their reflections. Music and image are folded, looped, stretched and compressed, linear time is transgressed in the hunt for The Moment, which never exists in a straightforward way but must be continually constructed, discovered, and rediscovered, created and interpreted. All sense of beginning and end break apart in the meeting with the spontaneity of the moment.
Keywords: 21st Century (2001-2100); Orchestral music; Multimedia